Ciclos biogeoquímicos en bosques de la Sierra de Bejar (provincia de Salamanca) - Santa Regina I.; Gallardo J.F. (Jornadas sobre las bases ecológicas para la gestión en ecosistemas terrestres, 1989)
Data of the bioelement cycles from the three forest systems are shown. The ecosystems are: a climax Quercus pyrenaica forest; a paraclimax Costanea sativa grove and a disclimax Pinus sylvestris forest. The three sites are near one from each other in the Candelario Basin (Salamanca province). Annual production average are proximately 7 Tm/ha in the coniferous forest and 6 Tm/ha in the deciduous forest; nevertheless, the difference between the decomposition indexes are very narrow, following the order: chestnut > oak > pine. The former expressed is according to a permanent organic matter accumulation of about 60 Tm/ha in the pine forest, 38 Tm/ha in the oak forest and 20 Tm/ha in the chestnut grove.
Jornadas sobre las Bases Ecológicas para la Gestión en Ecosistemas Terrestres, 1988/06/13-15, Zaragoza (Spain)